If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4y + -1) = 2(5y + 0.5) Reorder the terms: 3(-1 + 4y) = 2(5y + 0.5) (-1 * 3 + 4y * 3) = 2(5y + 0.5) (-3 + 12y) = 2(5y + 0.5) Reorder the terms: -3 + 12y = 2(0.5 + 5y) -3 + 12y = (0.5 * 2 + 5y * 2) -3 + 12y = (1 + 10y) Solving -3 + 12y = 1 + 10y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10y' to each side of the equation. -3 + 12y + -10y = 1 + 10y + -10y Combine like terms: 12y + -10y = 2y -3 + 2y = 1 + 10y + -10y Combine like terms: 10y + -10y = 0 -3 + 2y = 1 + 0 -3 + 2y = 1 Add '3' to each side of the equation. -3 + 3 + 2y = 1 + 3 Combine like terms: -3 + 3 = 0 0 + 2y = 1 + 3 2y = 1 + 3 Combine like terms: 1 + 3 = 4 2y = 4 Divide each side by '2'. y = 2 Simplifying y = 2
| 5+7x=17+x | | 5[3y-7]+3[7y-4]=18-2[8y+4] | | 5x+5=3x-13 | | 8+3=23 | | 2(x-4)=(x-5) | | f(x)=x^3+2x | | 2[x+4]-9=1 | | -4x-13=-2x-31 | | [t-8]=0 | | 2x-13=-5x-41 | | 2/√5= | | 0=18x^2+3x-6 | | A/-7-3=19 | | (3x-6)(4x+20)=0 | | [b+7]=5 | | -3h-2=16 | | 10/(3x7) | | 3/1/4 | | cos=-cos^2+sen^2 | | cos(x)=-cos(2x) | | (6x^2-5)-(2x^2+3x-2)= | | 144x^2+72x+9-1=11 | | 48r=9+r^2 | | (1/(6log(163)))ln(163) | | ax+v=22 | | aln163=1/6 | | 5x*5=-5 | | 99x-98=99 | | (7*10^5)/((2*10^-2)*(2.5*10^9)) | | n+m+N=20 | | f(x)=ln(x^2-4) | | z^2+2z+2=0completing |